STUDI EKSPLORATORI REFERENCE PRICE DAN FAKTOR YANG BERPERAN DALAM KEPUTUSAN KONSUMEN TENTANG HARGA - Dudi Anandya (Journal of Management and Business, 2005)
In Marketing Mix, Price usually consider as cost plus margin, but actually consumer develop more complicated thinking pattern when make decision about price. Prior study has reveal that consumer judge price base on reference price rather than actual price. This reference price classified into internal and external reference price. In this research the author try to broadening the theory using exploratory study to show that consumer not only comparing price in the same category, but also compare to complementary product. The result show that external reference price plays a dominant role in consumer decision